Morphological Characteristics and Elemental Composition of Magnetic Minerals from the Volcanic Activity of Lake Maninjau Sediments - Prasetyo, Ihsan Junira; Rifai, Hamdi; Syafriani, Syafriani; Putra, Rizaldi (Trends in Sciences, 2022)
Lake Maninjau has formed by the eruption of the Maninjau volcano, which spewed volcanic material to various places. This volcanic material contains various mineral-forming elements, one of which are magnetic minerals that accumulate in lake sediments. This research aims to determine the morphological characteristics and composition of magnetic mineral elements from volcanic activity in the sediments of Lake Maninjau, Agam Regency, Indonesia. Characteristics of morphological and composition of magnetic mineral elements originating from volcanic activity can describe volcanic eruptions in the past. So, this research is very important for paleo-eruption studies because it can be used as supporting information to determine the distribution of volcanic ash from a volcanic eruption in the past based on the magnetic properties of the material. The sample was selected from the core MAN 18-41B site 12 with a depth of 35 - 36 cm because it has a high magnetic susceptibility value. Morphological images of lake sediment magnetic minerals were viewed using a SEM instrument and EDS detector that shows the composition of the elements that arrange magnetic minerals. In general, the analysis of morphological images shows that the magnetic mineral grains in the Maninjau lake sediments are irregular and porous. This indicates that the magnetic minerals originate from volcanic activity. The image produced by Back Scattered Electron (BSE) has a difference in brightness on the surface of the magnetic grains, which indicates that the bright surface contains high Fe elements and the dark surface contains high Si. The spectrum generated by EDS shows that the dominant elements present in magnetic minerals in lake sediments are Fe, Ti and Si. Based on the morphology and elemental composition, it is indicated that the minerals contained in the sediments of Lake Maninjau come from volcanic activity. HIGHLIGHTS Lake Maninjau has formed by the eruption of the Maninjau volcano, which spewed volcanic material to various places. This volcanic material contains various mineral-forming elements, one of which are magnetic minerals that accumulate in lake sediments Characteristics of morphological and composition of magnetic mineral elements originating from volcanic activity can describe volcanic eruptions in the past Morphological forms can provide information about the source of magnetic minerals derived because magnetic minerals have different properties, types, and morphology depending on the source Maninjau Lake sediments are dominated by Iron (Fe), Silica (Si), and Titanium (Ti). Based on the morphological images and elemental composition, the magnetic minerals present in the Maninjau lake sediments are indicated to come from volcanic activity GRAPHICAL ABSTRACT